Smart textiles - Hossain, Md Raihan; Ahmed, Md Raju; Alam, Md Shamim (Textile progress, 2023)
Smart textiles, also known as electronic textiles or e-textiles, are advanced materials that merge traditional textile structures with integrated electronic components and technologies. These textiles offer enhanced functionality and capabilities by incorporating sensors, actuators, power sources, processing units, and communication systems. They enable interaction with the environment and other devices, going beyond the capabilities of traditional textiles. This paper overviews smart textiles and their applications in various sectors such as sportswear, industry, automotive, entertainment, military, public sector, healthcare, and safety domains. It also highlights recent advancements in the field. The focus is wearable fabric-based personal systems, including fitness monitoring, safety, security, and promoting a healthy lifestyle. Integrating smart textiles into garments and accessories can revolutionise industries and improve the quality of life by offering personalised and innovative solutions.